Effects in high cost in the issuance of a bank guarantee by commercial banks in Tanzania:The case of CRDB bank plc - Kalokola, Eustadius (Mzumbe Unversity, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the degree of Master of Science in Accounting and Finance of Mzumbe University